V-doped MoS2 nanozymes providing reactive oxygen species and depleting glutathione for photothermally-enhanced nanocatalytic therapy - Wang, Haiyan; Xia, Pengle; Kurboniyon, Mekhrdod S.; Fang, Shuhong; Huang, Kunying; Ning, Shufang; Jin, Guanqiao; Zhang, Litu; Wang, Chen (Frontiers in Pharmacology, 2024)
The tumor microenvironment and multidrug resistance of tumor cells seriously impair the activity of the nanozymes. Herein, a polyethylene glycol (PEG)-modified vanadium-doped molybdenum disulfide (V-MoS 2 @PEG) nanozymes were constructed to enhance anti-tumor activity through multi-enzymatic catalysis and photothermal effect with simultaneous reactive oxygen species replenishment and glutathione depletion. V-MoS 2 @PEG nanosheets exerted peroxidase activity by causing molybdenum ion (Mo 4+ ) to react with hydrogen peroxide to form toxic hydroxyl radicals (• OH). Meanwhile, the V-doping can deplete glutathione avoiding • OH consumption. In addition, the high heat generated by V-MoS 2 @PEG nanozymes under near-infrared laser irradiation brought about a desirable local temperature gradient, which produced an enhanced catalytic effect by promoting band bending. Furthermore, the photothermally inspired polarized charge increased the permeability of the tumor cell membrane and promoted further aggregation of the nanozymes, which realized the combination of photothermal therapy with multi-enzymatic catalysis, solved the problem of multienzyme catalysis, and improved the anti-tumor efficiency.